2017
DOI: 10.1123/mc.2015-0092
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Strategy During Regatta Starts in a Sailing Simulation

Abstract: In a sport conditioned by natural elements such as sailing, visual perception is a key factor for the performance. Research has shown that the visual behavior of athletes at different skill levels varies, which may cause differences in the performance achieved. The aim of this research was to examine the visual behavior of sailors from different ranking positions at the start of a race in a simulated situation. Twenty junior sailors (N = 10 top and N = 10 bottom ranking) participated in this study. The visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This would be a result to be taken into account, since we would then see a functional visual behavior, as indicated in other studies [19], which could allow sailors to optimize their visual search strategy. Further, these results are in line with those obtained by Manzanares et al [39], which showed that bottom-ranking sailors, who have a lower level of experience, performed fewer recurrent fixations on locations than top-ranking sailors. This more erratic visual behavior may be related to a higher complexity index, although this was not analyzed in that research study.…”
Section: Discussionsupporting
confidence: 92%
“…This would be a result to be taken into account, since we would then see a functional visual behavior, as indicated in other studies [19], which could allow sailors to optimize their visual search strategy. Further, these results are in line with those obtained by Manzanares et al [39], which showed that bottom-ranking sailors, who have a lower level of experience, performed fewer recurrent fixations on locations than top-ranking sailors. This more erratic visual behavior may be related to a higher complexity index, although this was not analyzed in that research study.…”
Section: Discussionsupporting
confidence: 92%
“…Age seems to be a key factor in choosing the most suitable route during the competition. The age of the sailor is significantly and negatively related to the distance travelled (r = −0.88; p < 0.01), with the oldest sailors being those who will use less time and distance to complete the competition course [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…When the sailor is sailing, he/she must carry out a decision-making process in order to interpret and respond to the stimuli of the environment, and such process is influenced by the ability to visualize [7]. This variable determines the spatial orientation of the sailor, and the greater the development of this capacity, the better the position in which he/she will be located in the starting area and the better the route chosen during the regatta will be, using the positions of buoys as a reference [8,9].…”
Section: Introductionmentioning
confidence: 99%